Sanksi Pidana Terhadap Tenaga Medis yang Memaksa Memberlakukannya Vaksin Covid-19 bagi Masyarakat yang Memiliki Riwayat Penyakit - Dendy Martono Prabowo; I Nyoman Gede Sugiartha; Ida Ayu Putu Widiati (Fakultas Hukum, Universitas Warmadewa, 2022)
he outbreak of the 2019 Coronavirus Disease that entered Indonesia which can be overcome by giving vaccines to the Indonesian people who meet the criteria according to the applicable law. However, the government requires the vaccination to be applied to all Indonesian citizens, even those with a history of disease, the government should guarantee the rights of everyone with the consent and without the slightest coercion in the voluntary vaccination process. This study aims to reveal criminal sanctions against medical personnel who force the implementation of the COVID-19 vaccine for people who have a history of illness. This study uses a normative juridical method by using a statutory problem approach. The sources of legal materials used are primary legal sources and secondary legal sources. The collected legal materials were analyzed systematically with descriptive presentation. Based on the results of the existing analysis, this study reveals that medical personnel who provide vaccines to people who have a history of illness can be said to have committed serious negligence which resulted in the recipient of the Health Service being seriously injured, the punishment for the maximum 3 (three) years in prison, even if it causes death, will be sentenced to 5 years. (five) years in accordance with the provisions of the Law of the Republic of Indonesia Number 36 of 2014 concerning Health Worker.